PENERAPAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM BERDASARKAN ASAL SEKOLAH - Al Ayyubi, Ibnu Imam; Noerzanah, Firda; Fitriyah, Dzul; Azizah, Azzah; Nuroh, Annisa Siti (STAI Ma'had Aly Al-Hikam Malang, 2024)
This research aims to see the relationship between students' critical thinking in the Think Pair Share (TPS), Think Pair Square (TPSq) Learning Models, and Conventional Learning through Lectures on Islamic Cultural History (SKI) material based on their school of origin. This research was carried out at SMPN 1 Cisarua, MTs Al-Hikmah Pasirhalang, and the Roudlotul 'Ulum Islamic Boarding School in West Bandung with quantitative research. The research instruments in this study used questionnaires and tests. The test for data analysis requirements used was Two Ways ANOVA with a data normality test using Kolmogorov-Smirnov with the help of SPSS version 26 software. In this study it was found that there was no difference in students' critical thinking abilities towards the TPS, TPSq, and conventional learning models, there was a difference in abilities. Students' Critical Thinking regarding the Origin of Middle Schools, MTs, and Islamic Boarding Schools, and the interaction between Learning Models and School Origin in determining Students' Critical Thinking Ability. Apart from that, there are differences in the critical thinking abilities of students who go to junior high schools and MTs, there are no differences in the critical thinking abilities of students who go to junior high schools and Islamic boarding schools. The significance value of MTs vs Islamic Boarding Schools is 0.038, and the difference in critical thinking abilities of students who go to MTs and Islamic Boarding Schools.